Challenges and Their Possible Solutions in the Ever-Changing Lake Balaton Region - Erzsébet Peter; Kornél Németh; Tamás Molnár; Katalin Molnárné Barna (DETUROPE)
We carried out this research focussing on the importance and local role of entrepreneurs in order to find out how “Balaton identity” can be developed and enhanced and which factors influence its existence. We are also interested in the way the political marketing for regionalisation can help the local inhabitants achieve higher living standards and form a bond with the region through small enterprises. The stronger and finer the bond is, the more active the local communities in the examined region are and they perform better in environmental, economic and social tasks. The potentials in “Balaton identity” may play an important role in future regional development. Health literacy, which promotes the cooperation between health care employees and the people, has become a new, important concept for the European Commission. If health literacy is integrated into the European Union Health Strategy that emphasises the increasing role of citizens, the efficiency of the health care system may improve and the burdens may decrease. The results are determined by the quality and the direct/indirect impacts of the working environment that affect our health condition in several ways. Consequently, one of the most important scenes for health promotion and health protection is the workplace. Workplace health promotion is clearly a profitable activity, since the employer, the employee and the social system all have interest in the benefits. Healthy, qualified and motivated workers increase the innovative potential and the productivity of the enterprise. Correct workplace health promotion also improves the company’s image among the clients and on the labour market.